Kehilangan Hasil Akibat Busuk Umbi dan Identifikasi Agens Penyebabnya pada Ubi Jalar di Kecamatan Cilimus, Kabupaten Kuningan, Provinsi Jawa Barat - Zahra, Atiqah Luthfi Anawati; Giyanto; Widodo (Jurnal Fitopatologi Indonesia, 2023)
Yield Loss Due to Tuber Rot and Identification of the Causal Agents in Sweet Potatoes in Cilimus District, Kuningan Regency, West Java ProvinceIn 2019 there was an increase in the incidence of tuber rot in sweet potato crops along with the prolonged rainy season which hit most of Java Island, causing yield losses. One of the affected areas was Cilimus District, Kuningan Regency, Province of West Java. This research was conducted to calculate the yield loss of sweet potatoes caused by tuber rot problems and to identify the causes in Cilimus District. Yield losses due to tuber rot ranged from 4.3% and 19.7% with an average of 9.4%. Compared with data on the decrease in sweet potato production in Cilimus District from 2018 to 2021, the tuber rot problem showed an essential role in decreasing production in the area. The results of the identification of the pathogen confirmed Ralstonia solanacearum was the causal agent of tuber rot. Based on the morphological symptoms, it was known that R. solanacearum is the main cause of tuber rot problems (56.8%), followed by Cylas formicarius (29.1%), and a combination of both (14.1%). The cropping patterns and cultivation techniques used by farmers were suspected of triggering the development of tuber rot problems in the research area.